Daya Tarik Dan Partisipasi Kelompok Masyarakat Desa Wisata Kopi Sidomulyo Kabupaten Jember - Luh Putu Suciati; Izza Afkarina (Diploma Travel Business, Faculty of Social and Political Science, Jember University, 2021)
The pattern of development of the Sidomulyo Coffee Tourism Village, Jember Regency in the new normal era can be judged from the level of attractiveness of the Tourism Village and the level of participation from community groups. This research aims to identify the potential objects of tourism appeal and potential natural interest, as well as aware of the participation rates performed by the group of the Cidomulyo Coffee Village. This research was held in the village of Sidomulyo Jember County. The sample used is as many as eight people and the group of Sidomulyo village as 21 people. The analysis method uses skoring analysis. Research results indicate that a component of good value attraction components are worth a pretty good, an amenity component tend to be involved in performing activities, quite often involved in performing activities, quite involved in performing activities, quite a development process